2019
DOI: 10.1016/j.triboint.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Polyetheretherketone (PEEK) transferred materials in a PEEK-steel contact

Abstract: Polyetheretherketone (PEEK) is a high performance polymer that can be an alternative to metal for some moving components in unlubricated conditions. During rubbing, PEEK is transferred to the counterface. The formation and properties of PEEK transfer films on steel and sapphire are studied by in-situ observations of PEEK wear process, contact temperatures and triboemission, as well as FTIR and Raman spectroscopies ex situ. Our results suggest that frictional heating alone may not be sufficient to generate PEEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…When the experimental velocity was 0.06 m/s, a certain amount of PEEK islands was found on the surface of the counter face parts after experiments (Figure 7). According to previous studies, the formation of PEEK polymeric transfer film on counter face parts was mainly due to its adhesion properties 8,12,13 . As the experiments went on, PEEK adhered on the counter face parts and formed the transfer film under high contact pressure 35 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…When the experimental velocity was 0.06 m/s, a certain amount of PEEK islands was found on the surface of the counter face parts after experiments (Figure 7). According to previous studies, the formation of PEEK polymeric transfer film on counter face parts was mainly due to its adhesion properties 8,12,13 . As the experiments went on, PEEK adhered on the counter face parts and formed the transfer film under high contact pressure 35 .…”
Section: Discussionmentioning
confidence: 87%
“…Both of the above factors would aggravate the adhesive wear of PEEK and promoted the formation of transfer film. The water film was hard to form under low experimental velocity, the transfer film would provide a good self‐lubricating property for PEEK specimens by changing the friction pairs from PEEK‐tin bronze to PEEK‐PEEK 12,13 . Hence, the average friction coefficient of PEEK under 0.06 m/s decreased continuously with the increase in the amount of transfer film (Figures 2 and 7).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They act as protective films avoiding the direct contact of PEEK with hard asperities of steel and thus reduce friction and wear. In-situ observation of the PEEK wear process was reported by Puhan and Wong [23] and suggested that PEEK wear debris ploughed by the asperities of the counter surface re-entered the contact and became trapped between asperities of the counter surfaces by compression, forming PEEK transfer films on the counter surfaces. Kalin et al [24] reported transfer-film thickness and coverage showed a good correlation with the friction and wear performances of PEEK and PEEK composites.…”
Section: Introductionmentioning
confidence: 87%
“…It has good high-temperature resistance, fatigue resistance, high strength and corrosion resistance. It has been widely used in aerospace, automobile and other fields [1][2][3][4][5][6][7][8][9]. The advantage of additive manufacturing (AM) technology is that it can quickly manufacture parts with complex structures and individual structures and has high material utilization [10].…”
Section: Introductionmentioning
confidence: 99%